A Catecholamine-Secreting Skull Base Sinonasal Paraganglioma Presenting with Labile Hypertension in a Patient with Previously Undiagnosed Genetic Mutation - Samuel Hahn; James N. Palmer; Nithin D. Adappa (Journal of Neurological Surgery Reports, 2012)
Abstract Sinonasal paragangliomas are very uncommon neuroendocrine tumors that can present as skull base lesions. Functional paragangliomas are exceedingly rare. They can be associated with genetic mutations that have been associated with increased risk of head and neck paragangliomas. We present a case of a rare functioning sinonasal paraganglioma of the skull base in a patient with distant history of prior abdominal paragangliomas. The patient underwent subtotal endoscopic resection of the skull base lesion limited by carotid encasement of the tumor. They were treated with postoperative adjuvant radiation and therapeutic metaiodobenzylguanidine (MIBG) therapy. Genetic testing revealed succinate dehydrogenase B (SDHB) mutation. Skull base paragangliomas are rare tumors that may preclude complete surgical resection. 131Iodine-MIBG can be used as adjuvant therapy in postoperative external beam radiation and in MIBG avid tumors. Long-term follow-up is needed given locally aggressive nature of these tumors, especially for patients with history of genetic mutations such as SDHB mutations as recurrent paragangliomas may develop.